2020
DOI: 10.1177/0267659120913803
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of antithrombin use during veno-venous extracorporeal membrane oxygenation in adults: rationale, current use, effects on anticoagulation, and outcomes

Abstract: Background: During extracorporeal membrane oxygenation, the large contact surface between the blood and the extracorporeal circuit causes a continuous activation of coagulation and inflammation. Unfractionated heparin, a glycosaminoglycan that must bind to antithrombin as a cofactor, is currently the standard anticoagulant adopted during extracorporeal membrane oxygenation. Antithrombin, beyond being a potent natural anticoagulant, acts in the cross-talk between coagulation and inflammatory system through anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 85 publications
0
9
0
1
Order By: Relevance
“…The analysis also revealed that crucial proteins regulating the aforementioned pathways are targeted by eight deregulated miRNAs ( Figure 4 bottom). During ECMO, due to both ARDS pathogenesis [ 17 , 41 ] and the continuous contact surface between the blood and the ECMO circuit [ 18 ], different coagulative pathways were also regulated by F2, FN1, MPL, and TBXA2R protein (which are known as positive regulators of these pathways) [ 18 , 42 , 43 , 44 ] and tissue factor pathway inhibitor (TFPI) (a negative regulator of coagulation processes) [ 45 ]. We found that let-7f, miR-25, miR-200b and miR-566 were up-regulated after 14 days of ECMO treatment in group B patients, and those miRNAs target the aforementioned positive regulators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis also revealed that crucial proteins regulating the aforementioned pathways are targeted by eight deregulated miRNAs ( Figure 4 bottom). During ECMO, due to both ARDS pathogenesis [ 17 , 41 ] and the continuous contact surface between the blood and the ECMO circuit [ 18 ], different coagulative pathways were also regulated by F2, FN1, MPL, and TBXA2R protein (which are known as positive regulators of these pathways) [ 18 , 42 , 43 , 44 ] and tissue factor pathway inhibitor (TFPI) (a negative regulator of coagulation processes) [ 45 ]. We found that let-7f, miR-25, miR-200b and miR-566 were up-regulated after 14 days of ECMO treatment in group B patients, and those miRNAs target the aforementioned positive regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during ECMO, several coagulative and inflammatory cascades similar to systemic inflammatory response syndrome (SIRS) are activated when the patient’s blood is exposed to the surface of the ECMO circuit [ 17 ]. Different miRNAs are able to regulate both platelet activation and crucial proteins involved in the regulation of hemostatic processes [ 18 , 19 ]. miRNA biomolecules also seem to play an important role in the regulation of gene expression during the pathogenesis of ARDS, being deregulated in pulmonary and extrapulmonary ARDS patients [ 20 ], as well as in patients with different severity status of ARDS [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acquired von Willebrand disease, thrombocytopenia, and bleeding are known complications in patients on ECMO [97][98][99][100]. Studies have described the use of VV ECMO without anticoagulation to reduce bleeding risks, however, the artificial contact surface of ECMO circuit itself causes continuous activation of coagulation, creating a prothrombotic environment [101,102]. The thrombotic risk is further accentuated in the presence of uninhibited COVID-19 diseases.…”
Section: Special Considerationsmentioning
confidence: 99%
“…In einigen Studien wurde über die Anwendung einer veno-venösen ECMO ohne Antikoagulation zur Verringerung des Blutungsrisikos berichtet. Allerdings führt die künstliche Kontaktoberfläche des ECMO-Kreislaufs selbst zu einer anhaltenden kontinuierlichen Aktivierung der Koagulation, wodurch ein prothrombotisches Milieu entsteht [101, 102]. Das Thromboserisiko wird durch das Vorliegen einer ungehemmten COVID-19-Erkrankung weiter verstärkt.…”
Section: Besondere üBerlegungenunclassified